PENGEMBANGAN PERANGKAT LUNAK DATABASE MONITORING KINERJA TPA - Wahyono, Heru Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
The increasing number of resident in an area impact to the increasing number ofdomestic waste produced by that area.The amount of existing landfill waste is notenough to accommodate all waste.This is the reason why the researchers need todevelop a landfill waste with good performance. Good performance landfill can treatwaste quickly and does not contaminate the environment. Methan gas produced by thelandfill waste can be used as alternatif energy resources. To improve the performance oflandfill waste, the waste management in landfill waste need to be monitored. The landfillwaste monitoring carried out on quality of leacate, volume and concentration of gas,and some other parameters. To facilitate the monitoring process should be developeddatabase software for landfill waste performance monitoring. With this software the datais managed in such a way so that it can be called back quickly and easily and can bedisplayed in various forms of landfill performance analysis reports